HOLDING THE EXECUTIVE TO ACCOUNT? Public Protector v President of the RSA 2021 (9) BCLR 929 (CC) - Swanepoel, Paul (Obiter, 2023)
This case is part of a growing body of jurisprudence relating to the Public Protector (PP). In particular, it concerns the PP’s mandate, contained in section 182 of the Constitution of the Republic of South Africa, 1996 (the Constitution), to “investigate any conduct in state affairs, or in the public administration, that is alleged or suspected to be improper or to result in any impropriety or prejudice”. The PP is further empowered in terms of the Public Protector Act (23 of 1994) (PP Act) to investigate, inter alia, maladministration, the unjustifiable exercise of power and dishonest conduct. In terms of this statutory framework, the PP’s primary function is to hold the executive to account. The Constitutional Court judgment that is the focus of this case note is an example of the PP attempting to hold the President accountable, but failing to do so as a result of producing an error-strewn report that was rejected by a full bench of the High Court and by a majority of judges in the apex court. On the facts, it is possible that had another PP produced a different report – one that satisfied the judges’ concerns – the President might have been less successful in avoiding public accountability. Apart from the main issue of the (at time of publication) now-suspended PP’s inability to hold the President to account, the judgment is significant from an administrative law perspective. In particular, the judgment adds to the debate on whether the PP’s remedial action amounts to administrative action. Although the Supreme Court of Appeal (SCA) held in 2018 that the PP’s remedial action does not constitute administrative action, the question has yet to be definitively dealt with by the Constitutional Court, with judges generally being content to leave the question open. Confusingly, the court a quo held that it was common cause that the PP’s reports do not amount to administrative action, but the judgment nevertheless made numerous references to the right to just administrative action. While Jafta J chose to leave the question open in Public Protector v President of the RSA (2021 (9) BCLR 929 (CC)), he engaged with the SCA’s judgment in Minister of Home Affairs v Public Protector (2018 (3) SA 380 (SCA) (Home Affairs)) and set out some guidelines on how the issue could be dealt with in the future.